DEVELOPING THE INTERACTIVE MAGIC AR BOOKS WITH GAMIFICATION FOR PROMOTE STORY BOOK - Yulyani Arifin; Dionisius Andrian Wangsadani; Bagaskara Akbar Fadhlillah; Mattheus Andrew Setiawan (Jurnal Ilmiah Informatika Komputer, 2022)
Children today tend to be more interested in playing with mobile phones than reading storybooks. The Interesting fairy tales from legends and traditional children's stories tend to be in the form of storybooks. And parents in the past often read fairy tales to their children. However, in modern times, each of them is busy with their mobile phone. Therefore, there is a need for a solution so children can be interested in reading fairy tale books without reducing the pleasure of playing games. The purpose of this research is to develop more interactive storybooks with Augmented Reality technology. The research method used is experimental research which starts from collecting data on needs through questionnaires and interviews with related parties, then analyzes and designs and manufactures prototypes which will be evaluated by usability testing and heuristic evaluation. From previous research, Augmented Reality technology has been widely applied in learning material. in schools and universities and also applied to the introduction of museums. From the storybooks themselves, there are already some who have implemented Augmented Reality or Gamification in applications. However, there is still no interaction between the user and the storybook. Therefore, this study develops an AR BOOK application where users can read storybooks while playing with Augmented Reality technology. The evaluation results show that the AR Book application can attract users to read stories from the application and users are entertained by this AR Book application. So it can be concluded that the addition of Augmented Reality and Gamification technology can attract the attention of users to read storybooks in a different way. For further development, traditional stories can be developed so that they can be better known by the younger generation.